TO QUESTION ABOUT POST-MODERN PROCESSES OF PREPARATION OF MASTER’S DEGREES IN INSTITUTIONS OF HIGHER EDUCATION OF KAZAKHSTAN (EXAMPLE - КАZNAU) - Ayupova Z.K.; Kussainov D.U; Uinston Nagan (Academic Journal of Physical and Chemical Sciences, 2019)
Undergraduates of KazNAU take part in the management of the university through student selfgovernment bodies representing and protecting students’ interests before the administration of the faculty and the university: make proposals on encouraging students for active scientific, educational and social activities; take part in solving social and housing problems; make suggestions for improving the educational process and research; interact with the administration, heads of the university departments, carrying out educational and educational work with students on various aspects of life activities; organize socially important social events for students. The students are the main consumers of the EP, therefore their interests are at the head of the implementation of this program.The main idea of student-centered education is aimed at forming an independent position in the process of study of undergraduates. Continuous analysis of the expected results is carried out by evaluating and discussing with the supervisors with undergraduates the results of the intermediate and final control through their processing and analysis.Master student within the development of OP, regardless of the form, direction and level of training, has the right to Express their disagreement in the form of an appeal.There are disciplines of a methodological nature aimed at the use of innovative technologies in the educational process, developed in conjunction with representatives of specialists in the field of jurisprudence. After that, the undergraduate is IPWM. The graduate student has the ability to check and analyze his progress through the electronic database of the university in an automated on-line mode.